Cranford - Gaskell, Elizabeth Cleghorn, 1810-1865; Ritchie, Anne Thackeray, 1837-1919; Thomson, Hugh, 1860-1920 (Salt Lake City, UT : Project Gutenberg, 2018)
"Cranford" by Elizabeth Cleghorn Gaskell is an episodic novel first published in 1853. Set in a small English country town, it affectionately portrays a society of genteel women$1 (Bmostly widows and spinsters$1 (Bnavigating life with "elegant economy" while clinging to old-fashioned codes of conduct. As the outside world encroaches through railways and social change, these proud ladies must reconcile their rigid class traditions with deeper values of kindness and mutual support. The novel chronicles a vanishing way of life with humor and warmth. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Cranford_(novel)
Release date is 2018-07-20
E-text prepared by KD Weeks, Anne Grieve, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: England -- Fiction; Sisters -- Fiction; Pastoral fiction; Villages -- Fiction; Older women -- Fiction; Female friendship -- Fiction